IDENTIFIKASI KECEMASAN SISWA DALAM MENYELESAIKAN MASALAH BANGUN RUANG SISI LENGKUNG BERDASARKAN TEORI VAN HIELE - OCTAVIANI CAHYANINGTYAS (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aimed to identify students’ anxiety in solving curved-surface solid geometry problems based on Van Hiele’s theory. The research employed a qualitative descriptive approach conducted at SMP Negeri 1 Ajung with students of class IXD as the participants. Data were collected through the Van Hiele Geometry Test (VHGT), curved-surface solid geometry tests, anxiety questionnaires, and interviews. The VHGT results indicated that students were classified into Level 0 (visualization), Level 1 (analysis), and Level 2 (informal deduction), from which one student from each level was selected as the research subject. The findings revealed that all subjects experienced anxiety when solving geometry problems, although at different levels. Students at Level 0 and Level 1 experienced moderate anxiety, while the student at Level 2 experienced high anxiety. The identified forms of anxiety included physiological, cognitive, and affective symptoms, such as trembling hands, excessive sweating, difficulty concentrating, hesitation in answering questions, fear of making mistakes, and thinking obstacles. The findings also showed that anxiety was influenced by both internal and external factors related to self-perception, academic demands, material complexity, and previous learning experiences in mathematics. It can therefore be concluded that anxiety affects the process of solving curved-surface solid geometry problems and is present across different van Hiele thinking levels. Accordingly, teachers are encouraged to design more supportive, interactive, and developmentally appropriate learning experiences to reduce students’ anxiety and improve their understanding of geometric concepts.
Keywords: student anxiety; curved-surface solids; van Hiele Theory; geometry; VHGT